Differences between official and non-official matches in worst-case scenarios in elite futsal players - Spyrou, K.; Freitas, T. T.; Marín-Cascales, E.; Herrero-Carrasco, R.; Alcaraz, P. E. (Baltic Journal of Health and Physical Activity, 2021)
Background: This study aimed to compare the worst-case scenarios (WCS) between official (OFF) and non-official (Non-OFF) matches, in different time-periods in an elite futsal team. Material and methods: Twenty-six games were divided into OFF (n = 13) and Non-OFF (n = 13). The WCS were calculated using: two methods, rolling averages (ROLL) and fixed-periods (FIX); four-length epochs (30-s, 1-, 3-, and 5-min); and player load per minute (PL·min-1). Results: Considering ROLL, significant and small differences were found in PL·min-1, with higher intensity in 30-s (p = 0.001; ES = -0.53) and 1-min (p = 0.001; ES = -0.47) in OFF when compared to Non-OFF, but non-significant and small to trivial changes in 3-min (p = 0.060; ES = -0.23) and 5-min (p = 0.605; ES = -0.06) were observed. Regarding FIX, significant and small changes were obtained, with higher intensity in OFF in all time-periods when compared to Non-OFF. Significant differences were found between the two methods (ROLL vs FIX) in 30-s, 1- and 3-min, but not in 5-min. Significant differences, with lower PL·min-1, were observed with increasing time-windows from both methods (p = 0.001). Conclusions: In summary, OFF matches present higher WCS than Non-OFF ones when considering short time-periods, and the FIX method could underestimate the "actual intensity" of the match compared to ROLL.